Perancangan Sistem Pengukuran Kinerja Program Studi Akademi Angkatan Udara Sebagai Kesiapan Menghadapi Era Society 5.0 - Sah Feroza; Gagat Riano; Ismoyo Ismoyo; Limawati Handayani (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
In order for the implementation of the academic ability basic potential development of the air dimension at AAU to be carried out efficiently, harmoniously and efficiently, a performance measurement system (SPK) design that is integrated with quality assurance is required. By using the IPMS method for the design and the AHP method for weighting, this study aims to develop a performance measurement system (SPK) in the AAU Department. From this research, 13 requirements, 25 objectives and 44 key performance indicators (KPI) can be identified which are grouped into 10 education components of Indoensian Airforce Arm Forces. The weighting results show that the curriculum criteria is the highest weight with a value of 11.52% and the lowest weight in the instruction package is 8.87%. While the largest weight of KPI is KPI NO 15B, namely the Conformity of RPS and SAP with Learning Outcomes with a value of 0.3764.